EFFECTIVENESS OF ISLAMIC EDUCATION INTEGRATION MODEL IN LEARNING ISLAMIC RELIGIOUS EDUCATION - Wulandari; Rossa Ramadhona; Dewi Sri Wahyuni (Adisam Publisher, 2024)
The science of Islamic education is not just the science of Islamic education, but the science of Islamic education, namely a systematic description of Islamic teachings regarding various aspects and components of education. Thus, knowledge of Islamic teachings regarding education can also be said to be part of the science of Islamic education. So Islamic education is the science of Islamic education, or the science of education from an Islamic perspective. Efforts to integrate general education with Islamic values cannot be separated from scientific universality which must be applied in the learning process without prioritizing scientific independence (looking for differences). The integration of Islamic education includes: First, the integrity of the Islamic value framework in each subject group is integrated as a whole (integral-holisitk). Second, the diversity of models, methods and integrated approaches with Islamic values as a normative framework can be used as a new perspective for educators in implementing the learning process. So that learning leads to the process of being a leader (being able to choose which ball to pick up) and a manager (knowing how to manage the ball) without being separated from the framework of Islamic values. Third, the integration of education implementation requires that the values of Islamic education in learning at school be applied in an integrated manner with the needs of society and families.